If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying P + 9p = 20 Solving P + 9p = 20 Solving for variable 'P'. Move all terms containing P to the left, all other terms to the right. Add '-9p' to each side of the equation. P + 9p + -9p = 20 + -9p Combine like terms: 9p + -9p = 0 P + 0 = 20 + -9p P = 20 + -9p Simplifying P = 20 + -9p
| 3x^3+18x^2+3x+18= | | -8a+2=-2(a+5) | | -5x+4y=-24 | | 2x^3(8x^2-5x+2)= | | 3+7x=6x-15 | | 36*25= | | 5*45= | | 10+5x=6x+22 | | 6*42= | | 3x+10=-3x+58 | | 2(x-3)=3x+7 | | x-9=2x+1 | | -6x-3=2x-75 | | x+10x+21= | | 2x^3+4x^2-30x=0 | | 4-x=-4x-17 | | 3xy+9x= | | 7x+5=6x-3 | | 2+2=98 | | 6(2x-5)=15-(5-8x) | | -3+3x=2x-13 | | 6x+7=13+5x | | n+2n=170 | | 9+2x=3x-1 | | 6b+3=3b-12 | | 6x+3=13+4x | | y-3y=4 | | X^9+8x^8-12x^7+8x^6= | | 7x-9=4x+3 | | 117-6x=2x+21 | | -3=2x+3 | | 95-4x=2x+11 |